2012
DOI: 10.3109/15419061.2012.749245
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exogenous ganglioside GM1 on different stages of cell spreading studied by directly quantifying spreading rate

Abstract: We developed novel methods to directly quantify cell spreading rate. By comparing our methods with traditional methods, we found that the enhancement effects of fetal calf serum (FCS) or the inhibitory effects of exogenous ganglioside GM1 occurred at different stages of cell spreading. GM1 mainly influenced the early and late stages of cell spreading of HUVECs. In the presence of 0.5% FCS, GM1 significantly impaired the area-based spreading rates (127.4  35.7 mm 2 /h and 22.2  3.8 mm 2 /h, respectively) on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…In presence of both integrin specific and unspecific ligands (fibronectin and vitronectin) the spreading curve became more linear and cells continued to spread radially even after 20 min from initial attachment. These data are consistent with other studies, as it was shown that serum promotes spreading but not initial attachment of 3T3, chicken embryonal fibroblasts and human skin fibroblasts (Edwards et al, 1993; Tucker et al, 1981; Verger and Imbenotte, 1990), and serum conditioning is not efficient for spreading of CHO and HUVEC cells (Edwards et al, 1993; Huang et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…In presence of both integrin specific and unspecific ligands (fibronectin and vitronectin) the spreading curve became more linear and cells continued to spread radially even after 20 min from initial attachment. These data are consistent with other studies, as it was shown that serum promotes spreading but not initial attachment of 3T3, chicken embryonal fibroblasts and human skin fibroblasts (Edwards et al, 1993; Tucker et al, 1981; Verger and Imbenotte, 1990), and serum conditioning is not efficient for spreading of CHO and HUVEC cells (Edwards et al, 1993; Huang et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…14,15) Briefly, HUVECs at 70% confluence were treated with or without 10 mM MβCD for 30 min at 37°C. The cells were then fixed by 4% paraformaldehyde, rinsed with PBS, and imaged in PBS by the confocal microscope.…”
Section: Methodsmentioning
confidence: 99%